Distributed travelling‐wave‐based fault location without time synchronisation and wave velocity error. Issue 8 (9th June 2017) - Ding, Jiali; Li, Lixue; Zheng, Yihui; Zhao, Chunming; Chen, Hongtao; Wang, Xin
Abstract : Existing single‐ and double‐terminal travelling‐wave fault‐location approaches have some disadvantages including difficulty in distinguishing the sources of reflect and refract waves, system error in time synchronisation and wave propagation velocity. In this study, a distributed travelling‐wave‐based fault‐location system, which eliminates the time synchronisation and wave propagation velocity error, is introduced. This novel system is consisted of three measurement points, which are located at both ends and the mid‐point of the line. At first, the measurement points, installed at both line ends, record the post‐fault current data for a time interval. The measurement point, located at the mid‐point, records the time tags of the three sequential wavefronts as t 1, t 2 and t 3 separately including the initial wave and following waves reflected at both the ends. Second, by comparing fault current recorded by the three measurement points, the fault interval can be determined based on current deviation theorem. Finally, travelling‐wave propagation velocity is calculated according to mathematic equation in terms of t 1, 2, 3 . Then, the fault point is located without the need of time synchronisation. The simulation and hardware tests match the theoretical analysis well, showing that the proposed location method provides not only high accuracy, but also good reliability.